2015
DOI: 10.1186/s13063-015-0878-8
|View full text |Cite
|
Sign up to set email alerts
|

Virtual restorative environment therapy as an adjunct to pain control during burn dressing changes: study protocol for a randomised controlled trial

Abstract: BackgroundThe pain of a severe burn injury is often characterised by intense background pain, coupled with severe exacerbations associated with essential procedures such as dressing changes. The experience of pain is affected by patients’ psychological state and can be enhanced by the anxiety, fear and distress caused by environmental and visual inputs. Virtual Reality (VR) distraction has been used with success in areas such as burns, paediatrics and oncology. The underlying principle of VR is that attention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 30 publications
1
24
0
6
Order By: Relevance
“…Two systemic reviews concluded that VR has the potential to be an useful analgesic tool, but more evidence is required 36 , 37 . With no randomized controlled trials except a single on-going trial 5 , it is important to check the long-lasting effect. In comparison within the group, the FTI group showed a significant improvement which was maintained at 3 weeks after discontinuation of the intervention; however, the improvement in HTI group lasted only one week.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two systemic reviews concluded that VR has the potential to be an useful analgesic tool, but more evidence is required 36 , 37 . With no randomized controlled trials except a single on-going trial 5 , it is important to check the long-lasting effect. In comparison within the group, the FTI group showed a significant improvement which was maintained at 3 weeks after discontinuation of the intervention; however, the improvement in HTI group lasted only one week.…”
Section: Discussionmentioning
confidence: 99%
“…However, all previous publications were case reports, case series, or pilot trials, except a single on-going randomized control trial by Small et al . 5 . Moreover, these investigations evaluated only the short-term analgesic effect and there are no reports about the long-term effects.…”
Section: Introductionmentioning
confidence: 99%
“…Computer Generated or CG-VR, e.g. ( Small, Stone, Pilsbury, Bowden, & Bion, 2015 ). Both approaches use a HMD with a head tracking system to generate instantaneous co-ordination of the user's head movements between the physical and virtual worlds ( Slater & Sanchez-Vives, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Virtual reality pain management for acute pain has been frequently studied and reviewed in both healthy subjects 11,25,80,81 and pain patients, especially burn victims 26,37,44,53,75,79 and patients with phantom limb pain. 1,68,73 One pioneering study was conducted on 2 adolescents, showing that they were able to better tolerate painful procedures during burn dressing changes during a VR experience.…”
Section: Acute Painmentioning
confidence: 99%